Malvinia escutiana, a new biostratigraphically important Oligocene dinoflagellate cyst from the Southern Ocean - Houben, Alexander J. P.; Bijl, Peter K.; Guerstein, Gladys Raquel; Sluijs, Appy; Brinkhuis, Henk (Review of Palaeobotany and Palynology)
The Eocene-Oligocene Transition (EOT, ~. 34. Ma) represents the culmination of Eocene cooling by the initiation of large-scale Antarctic glaciation. Recognition and correlation of the EOT in Southern Ocean sedimentary successions have been difficult as a result of the general lack of well-calibrated biostratigraphic markers. Here we describe an unusual hypnozygotic organic walled dinoflagellate cyst (dinocyst) that originated in the Southern Ocean in conjunction with the onset of major Antarctic glaciation as reflected by 'oxygen isotope event 1' (Oi-1).We restudied samples from Deep Sea Drilling Program (DSDP) Site 511 using Light Microscopy and Scanning Electron Microscopy and found that a taxon previously known as Forma T constitutes a new protoperidinioid dinocyst genus and species that we name Malvinia escutiana. Published and re-evaluated data from other Southern Ocean sites show that M. escutiana did not occur before the Oi-1 (33.7. Ma), emphasizing its potential as a useful biostratigraphic marker for this key interval in the Southern Ocean's Cenozoic climate history. Fil: Houben, Alexander J. P. Utrecht University; Países Bajos Fil: Bijl, Peter K. Utrecht University; Países Bajos Fil: Guerstein, Gladys Raquel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Geológico del Sur. Universidad Nacional del Sur. Departamento de Geología. Instituto Geológico del Sur; Argentina Fil: Sluijs, Appy. Utrecht University; Países Bajos Fil: Brinkhuis, Henk. Utrecht University; Países Bajos